Critical thinking transformation in the digital era: The effectiveness of e-module based on read-STEM in elementary school - Kusumawati Shindi Nur Rahmawati; Suratno; Rizki Putri Wardani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Critical thinking is an essential 21st-century skill students need to face global challenges. It involves the ability to analyse information deeply, present arguments objectively, and make evidence-based decisions. However, the level of critical thinking skills of elementary students in Indonesia remains relatively low. To address this issue, the development of suitable learning media is needed. This study aims to develop and test the effectiveness of an e-module based on Read-STEM in improving elementary students’ critical thinking skills. The research used the Borg and Gall development model, involving 4th-grade students from several elementary schools in Jember. Instruments were validation sheets and critical thinking skill tests. The validation results showed a validity score of 95.1%, categorised as “very valid.” The effectiveness test indicated an average N-Gain of 0.61, placing it in the “medium” improvement category. These results indicate that the Read-STEM-based e-module is a valid and effective learning medium. Furthermore, these findings have broader implications for other educational contexts, such as science or social studies, which require complex problem analysis and evidence-based reasoning. This research contributes to the existing body of knowledge on digital learning tools by providing a specific, practical framework that combines the strengths of the STEM approach with critical reading strategies, demonstrating its potential for developing higher-order thinking skills beyond the elementary level.